Scratch vs Excel: Enhancing Math Problem-Solving and Student Confidence - Indrajaya, Undang; Siti Sadiah; Rostina Sundayana; Nitta Puspitasari (Department of Mathematics Education Program IPI Garut, 2025)
Artikel “Scratch vs Excel: Enhanching Math Problem-Solving and Student Confidence” bertujuan untuk mengetahui perbedaan peningkatan kemampuan pemecahan masalah matematis dan Self Confidence siswa dalam pembelajaran Matematika dengan menggunakan aplikasi Scratch dan Microsoft Excel. Penelitian ini menggunakan desain quasi eksperimen dengan subjek penelitian kelas XII MIPA pada salah satu SMA di Kabupaten Garut yang dipilih berdasarkan purposive sampling. Metode pengumpulan data meliputi tes, angket, dan observasi. Teknik analisis data mencakup statistik deskriptif, Gain ternormalisasi dan uji independen dua sampel untuk menguji perbedaan peningkatan (N-Gain) antara dua kelompok. Penelitian ini dapat menjawab kebutuhan akan pendekatan pembelajaran yang lebih efektif dan relevan dengan kondisi siswa, dengan fokus pada dua aspek yaitu kognitif (kemampuan memecahkan masalah) dan afektif (self confidence). Pada penelitian ini ditemukan adanya perbedaan peningkatan kemampuan pemecahan masalah matematis dan self confidence antara siswa yang menggunakan media pembelajaran interaktif aplikasi Scratch dan Microsoft Excel. Di mana Scratch terbukti memberikan peningkatan yang lebih baik dalam kemampuan pemecahan masalah matematis dan self confidence, dibandingkan Excel. Ini menunjukkan bahwa media interaktif berbasis animasi/visual dapat meningkatkan motivasi dan pemahaman siswa. The article “Scratch vs Excel: Enhanching Math Problem-Solving and Student Confidence” is a study to compare the differences in the improvement of the ability of mathematical problem-solving and student self-confidence in learning mathematics by using Scratch and Microsoft Excel applications. This study used a quasi-experimental design with the research subjects of class XII MIPA at one of the high schools in Garut Regency which was selected based on purposive sampling. Data collection methods include tests, questionnaires, and observations. Data analysis techniques include descriptive statistics, normalized Gain and two-sample independent test to test the difference in improvement (N-Gain) between two groups. This study can answer the need for a learning approach that is more effective and relevant to the conditions of students, focusing on two aspects, namely cognitive (problem-solving ability) and affective (self confidence). In this study, it was found that there were differences in the improvement of the ability of mathematical problem-solving and self-confidence between students who used interactive learning media Scratch application and Microsoft Excel. Scratch was shown to provide better improvement in mathematical problem-solving ability and self confidence, compared to Excel. This suggests that animation/visual-based interactive media can increase students’ motivation and understanding.